Yu-gi-oh! GX. Vol. 1, A new hero!! - Kageyama, Naoyuki (Shonen Jump manga., 2007)
At the exclusive Duel Academy, fifteen-year-old Jaden gets stuck in the worst dorm and starts out at the bottom, where he must fight against all odds to prove to himself--and everyone else--that he can be the best Duelist ever.